"Thinking with" objects : saperi, spazi e tempi della tecnica in Gilbert Simondon - Bugiardini, Nicolò (Scenari, 2021)
In the present paper we will try to investigate some aspects of Simondon's thinking about the technique. The "thinking with" objects, which seems to us to effectively embody the orientation of Simondo-Nian research, will be the background to the entire contribution. On the one hand, it will be necessary to underline how this approach allows us to think about the technique in an original and fruitful way; on the other hand, "thinking with" will allow for the establishment of a dialogue between Simondon and some recent perspectives, which will emerge in the conclusion. A historical precedent, as well as an essential reference, of the Simondonian approach can be traced in the encyclopedist enterprise. At first, we will then compare the two projects, emphasizing points of contact and differences, focusing attention on the status of techniques in the whole of knowledge. In the second paragraph we will focus on technicality as a way of being in the world, examining the Simondonian description of the genesis of technicity in the original man / world coupling and trying to approach, to this genetic perspective, also a perspective historical. This, in order to find useful tools for investigating the status of technology in the contemporary world. Some guidelines will be mentioned in the conclusion of this investigation.